MEKANISME PERTAHANAN KECEMASAN TOKOH SUPARNI DALAM NOVEL BADUT OYEN KARYA MARISA JAYA DKK. (KAJIAN PSIKOANALISIS) - Muh. Saiful (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The focus of this study to describe the defense mechanisms of anxiety Suparni character in the Novel Badut Oyen by Marisa et al. This study is a qualitative research approach to literary psychoanalysis. The data source of this research is Novel Badut Oyen by Marisa et al. Data research in the form of sentences and paragraphs fragment. Data collection techniques in this study is documentation techniques. Data analysis techniques using interactive methods Miles Huberman.The results showed anxiety Suparni character in the Novel Badut Oyen by Marisa et al. include: The defense mechanism of anxiety Suparni Novel Badut Oyen by Marisa et al. include: (A) repression, when Suparni know that Oyen prefer Ratna; (B) sublimation when Suparni confront the ghosts Oyen who want to avenge his death; (C) projections do Suparni to Syamsul, villagers, Ratna, and Oyen; (D) the transfer is done Suparni to object objects such as glassware, table and to Syamsul and Rudi; (E) rationalization carried Suparni when believing spirits Oyen Oyen missed him and could not have killed him; (F) formation reaction do Suparni when dialogue with Iryanto that Suparni claimed not to know the news as well as the killing of terror ghost Oyen, Syamsul and Rudi; (G) regression performed Suparni when invited Oyen pray, think, and look positively disaster; (H) isolation done Suparni by constantly endure at home Oyen; (I) the intellectualization do Suparni by trying to shift the object of allegations of murder to murder locations Syamsul and smoothed to remove any trace; (J) undoing do Suparni form of physical behavior and nonphysical behavior that is repeated.